PREFERENSI LABEL, DAN PERSEPSI KEMUDAHAN MEMPEROLEH PRODUK TERHADAP KEPUTUSAN PEMBELIAN SAYURAN ORGANIK - Euis Dasipah; Dety Sukmawati; Rahmah Sofiatin (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
This study aims to determine the effect of label preference on purchasing decisions, the influence of perceived ease of obtaining organic vegetables on purchasing decisions and the influence of label preferences and perceived ease of obtaining organic vegetables on purchasing decisions.The results of the study showed that the perception of ease of obtaining products had a positive and significant effect on purchasing decisions with a total influence of 23,6%. The direct effect of the perception of the ease of obtaining a product for a purchasing decision is 17%, This means that the more easily consumers get organic vegetables, the decision of consumers to buy organic vegetable products is higher